A qualitative application of the Job Demand-Control-Support (JDCS) to contextualize the occupational stress correctional workers experience. Issue 2 (15th March 2022) - Ricciardelli, Rosemary; Carleton, R. Nicholas
ABSTRACT: Correctional workers are at increased risk for a variety of mental disorders relative to the general population. The increased risk appears associated with frequent exposures to a variety of potentially psychologically traumatic events; however, the Job Demand-Control model and the Job Demand-Control-Support model posit operational (job content) and organizational (job context) stressors as increasing risks for mental health challenges. In the current study, we explore the potential impact of operational and organizational stress on correctional worker mental health, identifying specific stressors that might be modifiable. Data were drawn from the reports provided by 158 participants completing a large survey that elected to respond to either of two open text boxes inviting feedback related to their mental health. Qualitatively mapping our results onto the Job Demand-Control-Support model indicates participants perceive themselves as experiencing iso-strain as a function of being in a high demand, low control, and low social support work environment complicated by under-recognized caregiving. Participant reports suggest increased consultation by management and increased training may help to mitigate the perceived negative impact of the current workplace on their mental health.